The application of unmanned vehicle systems during the course of maritime law enforcement - Wu, Weiyu; Sun, Qirui; Yang, Hua (Frontiers in Marine Science, 2025)
The evolving maritime security landscape and rapid advancements in intelligent technologies have increased the importance of unmanned vehicle systems (UVSs) in maintaining maritime security and order. This article employs comparative research methods to evaluate the respective capabilities of common UVSs, including unmanned aerial vehicles (UAVs), unmanned surface vehicles (USVs), and unmanned underwater vehicles (UUVs). It assesses their suitability for different maritime law enforcement missions and examines the potential risks posed by their application. The findings reveal that UVSs are highly versatile in conducting various maritime law enforcement missions. However, their use introduces complex legal challenges under existing international law, resulting in legal uncertainties that may hinder the responsible development and deployment of UVSs in this domain. In addition, UVSs face emerging cybersecurity threats related to networks, data, and artificial intelligence. In response, the article proposes establishing an evaluation framework that aligns law enforcement objectives, system capabilities, and associated risks to guide maritime agencies in determining strategic UVS deployment priorities. It also emphasizes the need to rely on subsequent state practice as a means of addressing the challenges posed by current international legal frameworks. Furthermore, enhancing security risk management through lifecycle strategies offers an effective way to support the broader adoption of UVSs in maritime law enforcement.